Allelopathic Effects of Bidens pilosa L. var. radiata Sch. Bip. on the Tuber Sprouting and Seedling Growth of Cyperus rotundus L. - Ming-Tung Hsueh; Chihhao Fan; Wen-Lian Chang (Plants, 2020)
Bidens pilosa L. var. radiata Sch. Bip. (BPr) had been found capable of excluding Cyperus rotundus L. (CR) from its vegetation in fallow fields. Both allelopathy and competition of BPr were able to limit the growth of CR, but this has not been extensively investigated. To verify the two effects of BPr on CR management, density-dependent experiments and interspecies competitions with the application of activated carbon were conducted. The effects of BPr soil and its residues on the reproduction of CR were also evaluated. The results showed that the residues of BPr reduced the growth (54–61% of control) and tuber number (58–71% of control) of CR in the 3 plants pot−1 treatment but not in higher density treatments. In the interspecies competition, BPr exhibited an allelopathic but not competitive effect on CR when activated carbon was absent. CR tuber sprouting was significantly suppressed when sowed in the BPr soil. Likewise, BPr residue mulch inhibited the CR plant density by 87% as compared to natural-occurring CR residue mulch in the field. This study revealed that BPr might have potential for use as a cover plant and allelopathic mulch to control CR in the agroecosystem.